Peningkatan Kreativitas Anak Usia Dini Melalui Cerita Bergambar pada Anak Didik Kelompok B Tk Al-Akhyar Kabupaten Bungo - Hermansyah, Hermansyah (ALAYYA : Jurnal Pendidikan Islam Anak Usia Dini, 2021)
Abstract Children's creativity to be improved, so learning must be interesting and fun. One way to increase creativity is through visual stories. This study aim to determine the increase in children's creativity through visual stories. This research is classroom action research. The subjects of this study were group B students of Alakhyar Kindergarten, Bungo Regency, during the second semester of the 2019/2020 school year. Data were collected through observations, field notes, interviews and documents. The results of this study indicate that there is an increase in children's creativity through illustrated stories, namely, pre-cycle creativity increased by 13.33%, increased creativity in children. cycle I was 6.67% and increased creativity in cycle II reached 80.00%. To increase children's creativity through picture stories, it is also supported by a number of indicators, namely creative response, long attention span, self-organization / self-confidence , build relationships or ideas/storytelling, develop imagination and add new vocabulary. The conclusion of this study is that illustrated stories can increase children's creativity.